The statute of the Italian European Public Prosecutor (Milan Law Review, 2022)
The powers and status of the Italian prosecutors operating in the European Public Prosecutor's Office must be defined not only on the basis of the supranational discipline, but also of the constitutional principles on the public prosecutor. The limitation of the internal functional independence of the European Delegated Prosecutor is compatible with the rules of the Constitution, with residual criticalities regarding the supervision mechanism by the European prosecutors. Instead, the thesis of the doctrine that excludes the application of the rule of the "full autonomy" of the magistrate at the hearing must be critically analyzed.
Keywords: independence; autonomy; European public prosecutor